Comparsion study of color stability between three type of composite resin for a specified period of time after subjecting it to the same finishing(In vitro study) - حداد, منذر; عصيفوري, يزن (Latakia University Journal -Medical Sciences Series, 2021)
The aim of study: This study aims to evaluate discoloration of three type of nano composite resin which are different with filling materials (87%, 78%, 65%) after subjecting it to the same finishing for a specified period of time(a week, two weesk,a month), and trying to find the best type of composite for color stability. Materials and methods: The test has been made for (20 samples of Grandio composite, 20 samples of Z350 XT composite, 20 samples of Z350 XT Flowable composite), this samples were performed using a glass mold to form dis-shaped specimens (10mm in diameter, 2mm in thickness) and were cured by the light curing and they have been finished and polished and flooded in cola. The specimens, colors measurement were mad after( a week, two weeks, a month), the color change were evaluated using ∆E by Eazy shade VITA device. The results: It was noticed that the color change was obvious on all samples. But this change was more noticeable on Z350 XT Flowable composite after a month of fooling, and Grandio composite was the least color changed.